Towards increased use of trypanotolerance: Current research and future directions. Proceedings of a workshop - Rowlands, G.J.; Teale, A.J. (International Laboratory for Research on Animal Diseases, 1994)
This workshop was conceived in recognition of the fact that, over the years, a great deal of research has been conducted on trypanotolerance. With the advent of new and powerful means to identify markers and genes controlling traits of interest, and with the developments in animal breeding bringing greater speed in dissemination of desirable genotypes, there is increasing interest in trypanotolerance as a way forward in trypanosomiasis control. It was felt that the time had come for a further look at trypanotolerance research and the prospects for utilization of the trait to improve productivity of livestock under trypanosomiasis challenge, with the overall objective of assisting planning of future ILRAD/ILCA collaborative activities in the area. The first part of the report presents and discusses the research on the biological, social and economic aspects of trypanotolerance. The salient points from the discussions were then used as a focus for subsequent roundtable discussions in the different areas (conservation, preservation, enhancement and propagation). In a final session, the workshop agreed a number of recommendations.